2021
DOI: 10.3389/fpsyt.2021.638272
|View full text |Cite
|
Sign up to set email alerts
|

Victims of the Terrorist Attacks in Belgium and Professional Mental Health Aid Barriers: A Qualitative Study

Abstract: Introduction: Terrorist attacks can cause short and long-term stress-reactions, anxiety, and depression among those exposed. Sometimes, professional mental health aid, meaning all types of professional psychotherapy, would be appropriate, but victims often delay or never access mental health aid, even up to a decade after the initial event. Little is known about the barriers terrorist-victims encounter when they try to access professional mental health aid.Method: Using a qualitative design, 27 people exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In the literature, it is well-known that people who have social support are more willing to access health care. 19,31 Along these lines, this study indicates that the absence of PS in the immediate period was more likely among those who reported not being able to count on someone to help with daily life. Conversely, the absence of PS in the medium-term was significantly more marked among those who did not feel socially isolated.…”
Section: Discussionmentioning
confidence: 66%
“…In the literature, it is well-known that people who have social support are more willing to access health care. 19,31 Along these lines, this study indicates that the absence of PS in the immediate period was more likely among those who reported not being able to count on someone to help with daily life. Conversely, the absence of PS in the medium-term was significantly more marked among those who did not feel socially isolated.…”
Section: Discussionmentioning
confidence: 66%
“…The relatively large dataset also adds to the strength of the study. Finally, for public health interventions and therapists, the insights of this study are invaluable, as very few studies try to provide insight into what emergency responders go through during their action, which is important, as victims, in general, have noted that they have the feeling of not being understood by therapists or their social support ( 17 ). Further studies should try to differentiate even more between the different stressors and post-action response, especially in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…These attacks were followed by a bombing in a metro station in Brussels. All over Belgium, emergency responders had to help victims of the attacks in a situation of constant threat, both at the place of the scene and at the hospitals ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pre-trauma data have rarely been available, yet a baseline assessment is essential to estimate the true impact of an event. Moreover, prior research has often relied on self-reported information on health service utilization, which may be unspecific and prone to recall bias [ 24 27 ]. More detailed, accurate and objective data on affected individuals’ utilization of different types of health services are needed to strengthen the public health preparedness and response to terrorist attacks and similar events.…”
Section: Introductionmentioning
confidence: 99%